1994
DOI: 10.1002/j.2334-5837.1994.tb01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Development of Software Requirements

Abstract: This paper (1) describes what the current literature identifies as qualities of good software requirements, (2) identifies and examines different categories of software requirement methods, and (3) concludes that methods used to develop software requirements, though not perfect, have advantages that can improve the development of requirements for any type of system. Twelve requirement qualities were identified from the literature and these were used to establish evaluation criteria for software requirement dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A number of authors, including Cox et al [13], Mar [28], and Wiegers [41], advocate focusing on specification of events and exceptional scenarios. Alexander [9] underlines that ''exception cases can often outnumber normal cases and can drive project costs''.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors, including Cox et al [13], Mar [28], and Wiegers [41], advocate focusing on specification of events and exceptional scenarios. Alexander [9] underlines that ''exception cases can often outnumber normal cases and can drive project costs''.…”
Section: Related Workmentioning
confidence: 99%
“…Research shows that non-identified events (some call them ''missing logic and condition tests for error handling'' [37]) are the most common cause of changes in requirements which result in requirements volatility and creeping scope. The importance of event-completeness has been recognized by many authors (although they do not use this specific term), including Carson [11], Cox et al [13], Mar [28] and Wiegers [41]. The approach they recommend is based on identification of events performed by experts using brain storming or other ''manual'' techniques.…”
Section: Introductionmentioning
confidence: 98%
“…are addressed (cf. the first characteristic for establishing requirements completeness in (Mar 1994)). Of course, the metamodel needs to contain "all categories".…”
Section: Related Workmentioning
confidence: 99%
“…A number of authors [5,7,14] have developed various numbers of attributes for requirements. The literature is not in total agreement about the meaning of these attributes.…”
Section: Characteristics Of Sound Requirementsmentioning
confidence: 99%